PENGARUH MEDIA VISUAL COLOR LIGHTS FLASHING TERHADAP KEMAMPUAN RITMIK SISWA GANGGUAN PENDENGARAN DALAM PEMBELAJARAN ANGKLUNG - Deliyud Ihkrom, Rima; Faiz Noormiyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The research problem of the rhythmic ability of students with hearing impairments in learning angklung is relatively low, the media used has not been able to provide visual support to help students understand the concept of rhythm, Visual Color Lights Flashing media has not been utilized to facilitate rhythmic understanding for students. The study aims to determine the effect of visual media Color Lights Flashing on the rhythmic ability of students with hearing impairments in learning angklung. The study was conducted at SLB Bina Siwi Bantul Yogyakarta in January to April 2026. This study is an experimental study with a quantitative approach, the number of samples is 8 students. Data collection uses tests and questionnaires. The instrument validity test uses product moment correlation and reliability test uses Alpha Cronbach. The classical assumption test uses normality and linearity tests. The data analysis technique uses non-parametric statistical methods with the Wilcoxon test. Based on the results of the study, it was concluded that there is a significant influence of visual media Color Lights Flashing on the rhythmic ability of students with hearing impairments in learning angklung. The results of the Z test calculated a significance value of 0.020 <0.05. The rhythmic ability of students with hearing impairments in angklung learning using the Color Lights Flashing visual media had an average score of 86.5, and the rhythmic ability of angklung learning without using the Color Lights Flashing visual media had an average score of 65.5.